The dance of change : the challenges of sustaining momentum in learning organizations - Senge, Peter, ....-; Kleiner, Art, ....-; Roberts, Charlotte, ....- (London : Brealey, 1999)
The Dance of Change, written for managers and executives at every level of an organization, reveals how business leaders can work together to anticipate the challenges that profound change will ultimately force the organization to face. Then, in a down-to-earth and clear format, readers will learn how to build the personal and organizational capabilities needed to meet those challenges. This book identifies universal challenges that organizations ultimately find themselves confronting, including "Fear and Anxiety"; the need to diffuse learning across organizational boundaries; the ways in which assumptions built in to corporate measurement systems can handcuff learning initiatives; and the almost unavoidable misunderstandings between "true believers" and nonbelievers in a company.